Commodity trade between the US and Korea and the J-curve effect. Issue 1 (2nd January 2017) - Bahmani-Oskooee, Mohsen; Xu, Jia; Saha, Sujata
ABSTRACT: Several studies have investigated the impact of currency depreciation on Korean trade balance with the rest of the world and have found no significant effects. Suspecting that these studies could suffer from aggregation bias, another group has disaggregated the Korean trade flows by its trading partners and has investigated the response of the Korean trade balance to depreciation using bilateral trade data between Korea and each of its trading partners. Again, in most instances, they have found no significant effect. In this paper, we concentrate on the bilateral trade between Korea and the US and disaggregate their trade flows further by industry. We investigate the response of the trade balance of 69 industries to currency depreciation and find that the trade balance of 48 industries are affected significantly by changes in the real exchange rate in the short run. However, short-run effects translate to long-run favorable effects only in 24 industries.